The Development of HOTS (Higher-Order Thinking Skills) Assessment Instrument Based on Numeration Literacy in Mathematics for Junior High School - Wardani, Nurul; Siregar, Tanti Jumaisyaroh (Indonesian Journal of Science and Mathematics Education, 2023)
This research aims to develop a HOTS (Higher-Order Thinking Skills) assessment instrument based on numeracy literacy. This research employed a research and development method with 4D models. Feasibility analysis, discriminating index, item difficulty level, and product practicality were used in data collection techniques. The results showed that the average value of the item validity was 85.1% which indicated that this product is suitable for use as an assessment instrument. The discriminating index test obtained a value of  0.11 in the weak category, and the item difficulty level test obtained a value of 60% in the moderate category. Furthermore, The product practicality test on 30 students yielded an average score of 67.25%, which means that this product is practical. Thus, the instrument developed is feasible and practical as a stimulus to train higher-order thinking skills and increase cognitive knowledge in mathematics learning. Future research is expected to develop instruments in other mathematical materials.